A study on regeneration of medicinal plant Polygonatum punctatum Royle ex Kunth via callus induction from leaves and petioles - Thi Tham, Dang; Thanh Hang, Nguyen Thi; Thai Vinh, Tran; Van Hoi, Quach; Kim Cong, Vu; Duy, Nong Van (Academia Journal of Biology, 2024)
Polygonatum punctatum Royle ex Kunth is a rare medicinal plant species in Vietnam, with rhizomes used as a tonic for kidney yang deficiency, for treating joint pain, and for pain relief. Overexploitation of natural medicinal plants has driven the need for propagation techniques to meet increasing demand, compensate for habitat degradation, and conserve rare species. In this study, tissue culture techniques were applied to investigate the effects of different growth regulators on the in vitro regeneration of P. punctatum. The results showed that sterilizing young leaf and petiole samples with 0.1% HgCl2 for 6 minutes achieved optimal effectiveness. The MS medium supplemented with 1.5 mg/L BA and 0.5 mg/L 2,4-D was identified as the most suitable for inducing callus formation from young leaves and petioles. The MS medium supplemented with 2.0 mg/L BA and 0.2 mg/L NAA yielded the best results for shoot regeneration, while the 1/2 MS medium supplemented with 1.0 mg/L NAA was appropriate for root formation. The in vitro propagation results of P. punctatum contribute to the conservation and sustainable development of this valuable medicinal plant and aim towards the rapid multiplication of healthy plantlets for commercialization.